2022
DOI: 10.1186/s12871-022-01943-8
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of ultrasound-guided anterior quadratus lumborum block for pain management following lumbar spinal surgery: a randomized controlled trial

Abstract: Background Quadratus lumborum block (QLB) is a fascial plane block. There is no randomized study on the efficacy of QLB for lumbar surgery. We evaluated the efficacy of QLB for postoperative pain management and patient satisfaction after lumbar disc herniation surgery (LDHS). Methods Sixty patients with ASA score I-II planned for LDHS under general anesthesia were included. We allocated the patients into two groups: the QLB group (n = 30) or the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
6
0
5
Order By: Relevance
“…After the USG evaluation was completed, participants were asked to rate their position experience using a 7-point Likert numerical comfort assessment questionnaire. 10 The stretcher comfort, position comfort, waist comfort, and abdominal comfort were scored as 1 (very bad) - 7 (perfect) for both positions.…”
Section: Methodsmentioning
confidence: 99%
“…After the USG evaluation was completed, participants were asked to rate their position experience using a 7-point Likert numerical comfort assessment questionnaire. 10 The stretcher comfort, position comfort, waist comfort, and abdominal comfort were scored as 1 (very bad) - 7 (perfect) for both positions.…”
Section: Methodsmentioning
confidence: 99%
“…Ademais, alguns homens estão mais expostos a atividades que aumentam o risco de hérnias inguinais, como levantar objetos pesados regularmente no trabalho ou praticar esportes que envolvem movimentos bruscos e esforços intensos. Esses fatores combinados contribuem para a maior prevalência de hérnias inguinais em homens, destacando a importância da conscientização sobre os fatores de risco e medidas preventivas 1,9 .…”
Section: Prevalência De Hérnias Inguinais Em Homensunclassified
“…Após a reparação, a incisão é fechada com suturas e o paciente é monitorado durante o período de recuperação. A cirurgia geralmente é realizada em regime de ambulatório, o que significa que o paciente pode retornar para casa no mesmo dia, embora o tempo de recuperação possa variar dependendo da extensão da cirurgia e da saúde geral do paciente 1,5 .…”
Section: Técnicas Cirúrgicasunclassified
See 1 more Smart Citation
“…Regrettably, both of these studies have since been withdrawn. In a more recent study examining the impact of QLB on postoperative pain management following lumbar disc herniation surgery, it was found that administering QLB after the surgery enhanced the patient’s comfort levels both during periods of rest (0 and 2 h postoperatively) and activity (0, 2, 4, 8, and 16 h postoperatively) 51 . Wilton et al 52 .…”
Section: Clinical Application Of Qlbmentioning
confidence: 99%